2011
DOI: 10.1007/s11916-011-0238-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation: A Review

Abstract: Spinal cord stimulation (SCS) is a safe and effective treatment of a variety of chronic pain conditions. As our understanding of the mechanisms of action and potential uses of SCS has evolved, clinical and technological advancements have followed. This review provides an overview of potential mechanisms of action of SCS, evidence for its effectiveness, potential complications, and highlights of developing areas of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…Although SCS is effective in most patients, the treatment is not without risks. Review studies report SCS to be a safe intervention in neuropathic pain patients (41,42). The most common complications related to SCS are hardware related (lead migration, lead fracturing, connection failure, and discomfort), infection, subcutaneous hematomas, and cerebrospinal fluid leak (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Although SCS is effective in most patients, the treatment is not without risks. Review studies report SCS to be a safe intervention in neuropathic pain patients (41,42). The most common complications related to SCS are hardware related (lead migration, lead fracturing, connection failure, and discomfort), infection, subcutaneous hematomas, and cerebrospinal fluid leak (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, SCS may produce enhanced release of g-aminobutyric acid and decreased release of glutamate at the dorsal horn, both contributing to decreased modulation of pain perception. 7 Acetylcholine has also been shown to be released with SCS and is associated with activation of the muscarinic M4 receptor.…”
Section: Mechanism Of Scs Specific To Tcsmentioning
confidence: 99%
“…7 Furthermore, SCS may produce enhanced release of g-aminobutyric acid and decreased release of glutamate at the dorsal horn, both contributing to decreased modulation of pain perception. 7 Acetylcholine has also been shown to be released with SCS and is associated with activation of the muscarinic M4 receptor. 7 In a review by Wu et al in 2008, a spinal cord stimulator was shown to produce antidromic activation of sensory fibers and decreased sympathetic outflow as well as an increase in vasomotor center activity and release of neurohumoral factors when placed in patients with vascular disease.…”
Section: Mechanism Of Scs Specific To Tcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases, SCS is a valuable option [49,117]. Still, many patients do not reach adequate pain control or experience troublesome side-effects [12,65].…”
Section: The Treatment Of Neuropathic Painmentioning
confidence: 99%